On the query complexity of estimating the distance to hereditary graph properties - Hoppen, Carlos; Kohayakawa, Yoshiharu; Lang, Richard; Lefmann, Hanno; Stagni, Henrique (SIAM journal on discrete mathematics, 2021)
Given a family of graphs $\mathcal{F}$, we prove that the normalized edit distance of any given graph $Γ$ to being induced $\mathcal{F}$-free is estimable with a query complexity that depends only on the bounds of the Frieze--Kannan regularity lemma and on a removal lemma for $\mathcal{F}$.
Gesehen am 19.09.2021